Impact of economic globalization on gender (in)equality in sub-Saharan Africa - Zheleznova, Aleksandra; Sejkora, Jiří, 1985-; Neumann, Pavel, 1956-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The term “globalization” is widely used in the explanation of the modern economic, cultural, social, and political changes in the world. Because of its complexity, globalization has an impact on many areas of life and affects the entire world. This diploma thesis focuses on the impact of economic globalization on the developing countries and on sub-Saharan Africa in particular. The thesis also focuses on the question of gender equality in the context of globalization. Globalization brings new information, technologies, and oррortunities to sub-Saharan Africa. Still, in some countries, women are marginalized and discriminated. Those countries are missing women’s potential to contribute to the country’s growth and development. The diploma thesis analyses the changes of women’s status in sub-Saharan Africa during the past decades with a special focus on economic, social, interpersonal, and political dimensions of women’s status. Zambia and Tanzania are selected as case-study examples to illustrate the changes in gender (in)equality in sub-Saharan Africa.
Vedoucí práce: Jiří Sejkora
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses